Ocular Drug Delivery into the Eyes Using Drug-Releasing Soft Contact Lens - Toshihiko Tashima (MDPI AG, 2024)
The impact of visual impairment, such as blindness, on quality of life is immeasurable. However, effective ocular drug delivery into the eyes has not yet been established, primarily due to the impermeability imposed by the blood-retinal barrier (BRB) based on the tight junctions and efflux transporters at the endothelium or the epithelium in oral or intravenous administration, as well as the dilution with tear fluid and excretion through the nasolacrimal duct in eye drop administration. Furthermore, intravitreous injections induce pain and fear in patients. Unmet medical needs persist in ocular diseases such as age-related macular degeneration and diabetic retinopathy. Therefore, innovative non-invasive administration methods should be developed. Drug-releasing soft contact lenses (DR-SCLs) affixed to the eye's surface can continuously and locally deliver their loaded drugs to the eyes. The use of DR-SCLs is expected to greatly enhance the bioavailability and patient adherence to the drug regimen. It is known that several solute carrier (SLC) transporters are expressed in various parts of the eyes, including the cornea, the ciliary body, and the bulbar conjunctiva. Carrier-mediated transport through SLC transporters may occur in addition to passive diffusion. Moreover, nanoparticles can be loaded into DR-SCLs, offering various intelligent approaches based on modifications to induce receptor-mediated endocytosis/transcytosis or to control the loaded drug release within this delivery system. In this perspective review, I discuss the implementation and potential of DR-SCL-mediated ocular drug delivery, particularly focusing on low-molecular-weight compounds because of their fine distribution in living body, ease of handling, and ease of manufacturing.